The conditions of academic education and the methodological preferences of young scientists: A systematic literature review - Jarota, Martyna (Kultura-Społeczeństwo-Edukacja, 2025)
This systematic literature review (SLR) collects and analyses publications on methodological preferences from almost the last 50 years. The aim of the review is to diagnose the state of knowledge as well as to integrate and synthesize the existing literature in the field of methodological preferences. This review concerns 73 texts that have been qualified for the study. The SLR reveals the need to reconstruct a seman-tic web, in which the notion of methodological preferences is embedded. Thus, it indicates the need to introduce a definition of methodological preferences, as well as to propose a model of this feature. Fur-thermore, some implications for future research are presented, along with the limitations of the systematic review of the literature.